O Brasil e o combate à apatridia no sistema interamericano de proteção dos direitos humanos. - Reis, Ulisses Levy Silvério dos (2016)
The focus of this dissertation is fixed on the forecasting and implementation of the right to nationality in normative documents and internal and international bodies as a responsible tool for eliminating the problem of not guarantee human rights to stateless persons. Under the inter-American system of human rights protection, both the American Declaration of the Rights and Duties of Man as the American Convention on Human Rights guaranteeing the right to nationality to anyone, but on the continent there are still millions of individual who can’t enjoy a nationality for discriminatory reasons. From this fact, it discusses up the measures taken by Brazil to combat statelessness and if there is a transnational way to treat it from an interaction of the states around the Organization of American States. The investigation is justified by the fact that Brazil regularly sponsor global meetings aimed to resolving the issue of the right to nationality of such individuals, as well as the need to increase the studies in our country about the human rights norms of the Organization of American States. The methodology follows the deductive model subject to hermeneutic and comparative procedures. The exploratory and descriptive work’s bias is presented based on the analysis of international standards norms for protection of right to nationality, while comparing it under the light of Brazilian legal system will present proposals about the appropriateness or the need to improve the internal regulatory framework. The work is divided into four chapters. In the first, the concepts concerning the right of nationality and statelessness phenomenon will be displayed, their most common causes and the breaking point identified by Hannah Arendt in relation to the failure of the standard of human dignity to guarantee rights to those who do not enjoy a nationality. The second presents the development of international human rights law with regard to nationality. The next section reviews the milestones of the Brazilian law regarding the treatment of stateless persons, with an emphasis on its shortcomings and promoting a comparison – at legal level – with other Latin American countries. The last chapter discusses the Habermas’s proposal to form transnational states and how could such architecture contribute to the protection of stateless persons. The research shows that Brazil, despite having ratified the universal conventions on statelessness and be a signatory of the San José Pact, has an insufficient legal frame for the protection of these people which entails helplessness on the part of official institutions and violation of their basic rights of citizenship; at the same time, the formation of a transnational state based on the Organization of American States set up the possibility of ensuring the protection of stateless in the continent through the construction of a discursive and normative public sphere common to people and governments.